2020
DOI: 10.1021/jacs.0c04140
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Access to Highly Substituted Vinyl Ethers via trans-Difunctionalization of Alkynes with Alcohols and Iodine(III) Electrophile

Abstract: A method for the regio-and stereoselective synthesis of highly substituted vinyl ethers via trans-1,2-difunctionalization of alkynes with a cyclic λ 3-iodane electrophile (benziodoxole triflate) and alcohols is reported. The reaction tolerates a variety of internal and terminal alkynes as well as various alcohols, affording β-λ 3-iodanyl vinyl ethers in good yields with high regio-and stereoselectivities. The benziodoxole moiety of the products can be used as a versatile linchpin for the synthesis of structura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 54 publications
0
39
0
6
Order By: Relevance
“…Through isotope-shift experiments (please see Supporting Information File 1 ), it was possible to establish that the aryl ketone of the product contains the 18 O atom (Δδ C = 4.42 Hz) [ 57 59 ]. Formation of the corresponding enol [ 60 ], tautomerisation and displacement liberates the α-fluoroketone and regenerates the ArI catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Through isotope-shift experiments (please see Supporting Information File 1 ), it was possible to establish that the aryl ketone of the product contains the 18 O atom (Δδ C = 4.42 Hz) [ 57 59 ]. Formation of the corresponding enol [ 60 ], tautomerisation and displacement liberates the α-fluoroketone and regenerates the ArI catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the blank experiment results, and previously reported related synthesis reactions, [2j,12a,16] we proposed the reaction mechanism for preparation of pseudocyclic β‐trifluorosulfonyloxy vinylbenziodoxolone 7 and β‐azido vinylbenziodoxolone 10 (Scheme 8). Firstly, IBAs 5 react with TfOH to generated IBA‐TfOH 6 in the reaction mixture.…”
Section: Figurementioning
confidence: 95%
“…Several research groups have reported general synthetic procedures for the preparation of vinylbenziodoxolones by addition of various nucleophiles to the triple bond of alkynylbenziodoxolones, [2g,h,k,3] or by reactions of activated hydroxybenziodoxole (IBA) with alkynes [2j,4] or alkenylboronic acids [2a,e] . In 2015, our group reported preparation of the pseudocyclic vinylbenziodoxolone derivative 7 a by the reaction of a highly electrophilic IBA‐TfOH 6 with trimethylsilyl‐substituted acetylene (Scheme 1).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Here, PIDA serves as a decarboxylative reagent and as a source of iodonitrene, promoting electrophilic amination of the resulting imine, which gives a diazirine after oxidative cleavage of the iodine species. Inspired by these elegant synthetic methods and our long-term interest in both catalytic [3 + 2] cycloaddition reactions , and hypervalent iodine­(III) chemistry, we were curious about the potential outcomes of the electrophilic amination of pyrrolidines using iodonitrene, which has not been documented (Figure D). Here, we report a mild and efficient method for the highly stereoselective synthesis of cyclobutanes carrying diverse functionalities with different substitution patterns from readily accessible pyrrolidines using iodonitrene chemistry.…”
mentioning
confidence: 99%